A review on control systems hardware and software for robots of various scale and purpose. Part 3. Extreme robotics - A. M. Romanov (Российский технологический журнал, 2020)
A review of robotic systems is carried out. The paper analyzes applied hardware and software solutions and summarizes the most common block diagrams of control systems. The analysis of approaches to control systems scaling, the use of intelligent control, achieving of fault tolerance, reducing the weight and size of control system elements belonging to various classes of robotic systems is carried out. The goal of the review is finding common approaches used in various areas of robotics to build on their basis a uniform methodology for designing scalable intelligent control systems for robots with a given level of fault tolerance on a unified component base. This part is dedicated to extreme robotics and the generalization of the conclusions for the whole review. The paper notes the possibility and necessity of developing common approaches to the creation of robots of various sizes and purposes. It is noted that, in contrast to many foreign countries, in the Russian Federation developers must consider the serious limitations on the electronics components, which do not allow for the free conversion of technologies between civilian, military and space robotics. In this regard, it is proposed to analyze the interchangeable Russian and foreign microelectronic components, to find technical solutions in the field of the control systems and communication between them, which could be implemented both in foreign and Russian microelectronics, and to create on their basis a conceptual model of scalable intelligent control system with a required level of fault tolerance. The model should be based on a unified set of components.